THE CORRELATION BETWEEN TEACHERSÃ¢â¬â¢ WORKING PERIOD AND WORKLOAD AND STUDENTSÃ¢â¬â¢ ENGLISH ACHIEVEMENT OF SOME JUNIOR HIGH SCHOOLS IN PALEMBANG CITY - Septarini, Dian (English Community Journal, 2017)
The Objective of this study is to find out whether or not there is a significant relationship between teachersÃ¢â¬â¢ working period and workload and studentsÃ¢â¬â¢ English achievement of some Junior High Schools in Palembang city. The populations of this study were all English teachers and the students of ten Junior High Schools in Palembang. 945 students were taken as the sample by using purposive sampling and for the teachers was also purposive technique sampling. The instrument used in collecting the data were questionnaire for teachers that was used to know the ideal condition of teachersÃ¢â¬â¢ working period and workload and documentation of studentsÃ¢â¬â¢ English achievement. The data obtained from the questionaire and studentsÃ¢â¬â¢ grade was analyzed by using Coefficient Contingency on the help of SPSS Package for Windows to assess the contribution of teachersÃ¢â¬â¢ working period and workload and studentsÃ¢â¬â¢ English achievement. The obtained chi-square is 14.594, the probability under 0.05 and degree of freedom 4. The chi-square obtained > the value of chi-square table and coefficient contingency value is 0.542. It means that there was a correlation between teachersÃ¢â¬â¢ working period and workload and studentsÃ¢â¬â¢ English achievement.